Lipodystrophy frequency according to insulin treatment regimen in type 2 diabetic patients: Is insulin injection frequency matters in analog insulin era - YAVUZ, DİLEK (My University, 2022)
© 2022, Acta Endocrinologica Foundation. All rights reserved.Objectives. We aimed to determine lipodystrophy frequency according to insulin treatment regimen and insulin injection frequency in type 2 diabetic patients. Methods. A total of 345 type 2 diabetic patients under insulin treatment for at least one year were included in this cross-sectional study. Patients were examined for presence of lipodystrophy, insulin injection frequency and dosage. Lipodystrophy was evaluated with visual inspection and palpation of all injection sites. Patients were evaluated into three categories according to daily insulin dose requirement: Group 1= Standard-dose insulin users 0.6 U/ kg/day; Group 2= Medium-dose insulin users 0.61-1.9 U/kg/ day, Group 3= High-dose insulin users ≥2 U/kg/day. Results. Lipodystrophy was seen in 28% of the patients. Lipodystrophy was significantly higher in group 3. There was no significant difference between the groups in terms of lipodystrophy size. Duration of insulin treatment, daily total insulin dose, daily insulin dose per weight and number of daily insulin injections were significantly higher in the group with lipodystrophy. Daily injection number of long-acting, rapidly-acting analog and total insulin injections were significantly higher in group 3 than group 1 and 2. Number of daily insulin injections and lipodystrophy frequency were significantly higher in basal-bolus insulin user group. Multivariate analysis showed that insulin injection frequency is the independent risk factor for lipodystrophy. Conclusion. Lipodystrophy is still a clinical problem in patients with high-dose insulin requirement and frequent insulin injections. Reducing daily insulin requirement and daily number of injections should be given priority in the management of patients to prevent the development of lipodystrophy.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endokrin ve Otonom Sistemler; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Endocrine and Autonomic Systems; Diabetes Mellitus Type 2; insulin; lipoatrophy; lipodystrophy; lipohypertrophy; Diabetes Mellitus Type 2; insulin; lipodystrophy; lipohypertrophy; lipoatrophy